Rancangan Akademi Sepak Bola Berbasis Arsitektur High-Tech di Kabupaten Sinjai - Arifin, Muhammad Zuhri; Marwati, Marwati; Rahayu, Irma (TIMPALAJA : Architecture Student Journals, 2024)
PERSSIN, the main football club of Sinjai Regency in eastern South Sulawesi, has been established since 1970. Although the people in this area are very fond of football, the lack of sports facilities hinders their progress. As part of the 2020 work plan of the Sinjai Regency Youth and Sports Office, it will be very important to build a football academy that can assist in education and training from an early age. The focus of this research is on how high architectural concepts can be applied in the design of a football academy in Sinjai Regency. The aim of this research is to utilize advancements in science and technology to create innovative, effective, and sustainable designs. The methods used include literature research on advanced architectural principles as well as space needs analysis that supports the training and development of young athletes. The research results show that the application of advanced ideas can produce facilities that are modern, efficient, and adaptive to technological advancements, which will enhance the quality of training and support the achievement of football accomplishments in the region.